2017
DOI: 10.1016/j.celrep.2017.03.025
|View full text |Cite
|
Sign up to set email alerts
|

The Mutational Landscape of Circulating Tumor Cells in Multiple Myeloma

Abstract: Summary The development of sensitive and non-invasive “liquid biopsies” presents new opportunities for longitudinal monitoring of tumor dissemination and clonal evolution. The number of circulating tumor cells (CTCs) is prognostic in multiple myeloma (MM), but there is little information on their genetic features. Here, we have analyzed the genomic landscape of CTCs from 29 MM patients, including eight cases with matched/paired bone marrow (BM) tumor cells. Our results show that 100% of clonal mutations in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 22 publications
2
99
0
Order By: Relevance
“…Single-cell analyses have revealed that CTCs often comprise a heterogeneous population of cells. Logically, this heterogeneity may reflect the extent of intratumor heterogeneity (ITH) [65][66][67][68][69][70] and may have important implications for prognosis and resistance to therapy. Indeed, a recent study of archived samples from patients with metastatic breast cancer found 85% concordance between CTCs and metastatic sites in terms of mutations and copy-number profile [71].…”
Section: Ctc Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…Single-cell analyses have revealed that CTCs often comprise a heterogeneous population of cells. Logically, this heterogeneity may reflect the extent of intratumor heterogeneity (ITH) [65][66][67][68][69][70] and may have important implications for prognosis and resistance to therapy. Indeed, a recent study of archived samples from patients with metastatic breast cancer found 85% concordance between CTCs and metastatic sites in terms of mutations and copy-number profile [71].…”
Section: Ctc Heterogeneitymentioning
confidence: 99%
“…CTCs have also recently been suggested to be useful as a non-invasive tool to investigate the mutational landscape of progressing cancers [12,73]. For example, in multiple myeloma, the analysis of CTCs and matched bone marrow-derived tumor cells showed a high concordance in somatic mutations [69,108,109] and at the transcriptional profile level [68]. An additional study of metastatic breast cancer reported 85% concordance in single-nucleotide variant (SNV) mutations and copy-number alterations (CNAs) between paired CTCs and metastases [71].…”
Section: Clinical Value Of Ctcsmentioning
confidence: 99%
“…93 Genomic analysis of multiple myeloma CTCs has demonstrated particularly strong potential for not only prognosis but also the development of personalized treatments. 94 Although to our knowledge little clinical research exists regarding the use of CTCs and lymphoma, tumor cell DNA has shown promise for several lymphomas, including aggressive B-cell lymphoma, 95 other non-Hodgkin lymphomas, 96 Hodgkin lymphoma, follicular lymphoma, mantle cell lymphoma, diffuse large B-cell lymphoma, and primary CNS lymphoma. 97 Leukemia is unique among cancers in that the normal state of leukemic cells is circulating in the blood.…”
Section: Ctcs and Blood Cancersmentioning
confidence: 99%
“…Although to our knowledge research is sparse, many specialists believe that liquid biopsies in patients with multiple myeloma have demonstrated great potential; preliminary research has indicated that CTCs are promising as both prognostic and predictive biomarkers for disease recurrence and response to therapy . Genomic analysis of multiple myeloma CTCs has demonstrated particularly strong potential for not only prognosis but also the development of personalized treatments …”
Section: Introductionmentioning
confidence: 99%
“…CTCs are considered as ‘seeds’ distributed by primary tumors for potential initiation of metastatic growth at distant organ sites. CTCs reflect tumor heterogeneity, and could be genotyped and functionally characterized to study and target the evolving mutational landscape of primary and/or metastatic tumors [35]. …”
Section: Introductionmentioning
confidence: 99%